Kontribusi Mahasiswa melalui Pembagian Sembako dan Buku bagi Masyarakat Kurang Mampu sebagai Aksi Kepedulian Sosial - Masfufah Masfufah; Najma Alyaa Kamilah; Rahayu Mardikaningsih; Didit Darmawan; Mochammad Waliyul Hakim (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service activity aims to foster social solidarity and empathy for the inequality faced by underprivileged communities through a program of distributing basic food packages and donating books, implemented by students at Sunan Giri University, Surabaya. This program is a form of social responsibility oriented towards fulfilling the community's basic needs while simultaneously increasing access to learning resources. The program implemented the Asset-Based Community Development (ABCD) approach, which focuses on identifying and utilizing the community's assets and potential. A SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis was also used as a tool to support program planning and implementation. The results indicate that the distribution of basic food packages and book donations benefited the target community by helping them meet their basic needs and improving access to knowledge resources. This activity also contributed to strengthening social solidarity, increasing student awareness of community conditions, and supporting efforts to improve the quality of human resources. Thus, this community service program represents a tangible contribution from higher education institutions in supporting community welfare and empowerment.